Real-Time Implementation of a Novel Design Approach for Sub-GHz Long-Range Antenna for Smart Internet of Things Communication - Sneha Bhardwaj; Praveen Kumar Malik; Anish Gupta; Rajesh Singh (International Journal of Antennas and Propagation)
This research article designs and develops a planar small-size antenna design for smart Internet of Things (IoT) communication with long-range technology (LoRa). The proposed system is best suited for transceiver systems in this automation and sensing era. In the proposed antenna, the ground, the radiating element, and the stub feed are designed on the same side of the substrate, keeping in mind that it can print the LoRa module. The design consists of a meandered monopole, a dipole structure as a ground, and a stub feed. A different design approach is employed to get an optimized result. The antenna is made up of a rectangular feed stub to which a connecting wire is attached. The overall dimension of the antenna is 55 m × 55 m × 1.6 mm. To verify the proposed design, an antenna was fabricated and measured, which covers the LoRa frequency band at 868 MHz, providing a sufficient bandwidth of 10 MHz and a gain of more than 0.5 dB in the operating band. A designed antenna is implemented for sensor data communication with the LoRa module device and device interface Arduino platform. The antenna is connected as a transmitter and receiver one by one to verify its performance with machine-to-machine communication using the LoRa module. The size, bandwidth, and radiation efficiency of this antenna are better than the antennas in the literature. The designed antenna is successfully implemented with LoRa connectivity and communicates the data up to 8 km in line-of-sight communication, more than 1 km in urban environments, and approximately 250 m of connectivity in building areas.